Impact of the “Low-Carbon City Pilot” Policy on Energy Intensity Based on the Empirical Evidence of Chinese Cities - Hong, Min; Chen, Shuanglian; Zhang, Kexian (Frontiers in Environmental Science, 2021)
Reducing energy intensity is conducive to the sustainable use of non-renewable fossil energy, and is also one of the main strategies to deal with climate change and environmental degradation. The effect of national macro-level factors on energy intensity has been basically confirmed, but the effect of regional low-carbon policy remains to be investigated. Based on this, our analysis exploits China’s “low-carbon city pilot” policy as a quasi-natural experiment and conducts the difference-in-difference resign. We collect the panel data of 271 cities in China from 2006 to 2016. The empirical results show that: first, the low-carbon city pilot policy can effectively reduce the energy intensity. Second, there exist heterogeneous effects on energy intensity among different cities, and the inhibition effects in eastern cities, high economic development cites, and non-old industrial-base cities are more significant. Third, the policy mainly affects regional energy intensity through technological innovation rather than industrial structure optimization mechanism.